The UX entrenchment enigma : why user experience practices are not being incorporated in South African enterprises' Information Systems Development Methodologies (ISDMS) - Gelderblom, Helene (University of Pretoria, 2018)
Dissertation (MIS)--University of Pretoria, 2017.